The changing landscape of treatment for acquired hemophilia A - Massimo Franchini; Daniele Focosi (Bleeding, Thrombosis and Vascular Biology)
Acquired hemophilia A (AHA) is a rare acquired autoimmune disorder caused by autoantibodies against coagulation factor VIII (FVIII), which cause a hemorrhagic diathesis, not rarely of severe degree. Standard treatment consists of bleeding control with bypassing agents (recombinant activated factor VII and activated prothrombin complex concentrate) and recombinant porcine FVIII, and immunosuppressive therapy (corticosteroids with or without cyclophosphamide). Recent studies have renewed the interest towards the immunosuppressive agent rituximab for FVIII inhibitor eradication and have suggested a potential role for emicizumab for the prevention of bleeding in AHA patients. This narrative review will focus on the placement of these two emerging drugs within the treatment landscape for AHA.